2022
DOI: 10.3389/fpls.2022.972734
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and comprehensive analyses of NAC transcription factor gene family and expression analysis under Fusarium kyushuense and drought stress conditions in Passiflora edulis

Abstract: The NAC gene family is one of the largest plant transcription factors (TFs) families and plays important roles in plant growth, development, metabolism, and biotic and abiotic stresses. However, NAC gene family has not been reported in passion fruit (Passiflora edulis). In this study, a total of 105 NAC genes were identified in the passion fruit genome and were unevenly distributed across all nine-passion fruit chromomere, with a maximum of 48 PeNAC genes on chromosome one. The physicochemical features of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 147 publications
3
14
0
Order By: Relevance
“…In this study, most of the AsNAC proteins had all of the five subdomains, whereas some domain regions were incomplete in the minority proteins. Similar results were also observed in some previous studies ( He et al, 2022 ; Yang et al, 2022 ), indicating that some NAC proteins possessed preternatural structures and unique functions. It is reported that subdomains A, C, and D are more conserved than B and E ( Ooka et al, 2003 ; Wang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, most of the AsNAC proteins had all of the five subdomains, whereas some domain regions were incomplete in the minority proteins. Similar results were also observed in some previous studies ( He et al, 2022 ; Yang et al, 2022 ), indicating that some NAC proteins possessed preternatural structures and unique functions. It is reported that subdomains A, C, and D are more conserved than B and E ( Ooka et al, 2003 ; Wang et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our findings were inconsistent with the analysis of Passiflora edulis NAC protein interactions. This we related to the differences in the development processes of LchibZIP proteins and PeNAC proteins long-term domestication ( Yang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that StATG8 genes can be regulated using the WRKY transcription factor [ 42 ]. From the previous reports, autophagy plays an important role in development [ 43 , 44 ]; the regulatory elements CCGTCC motif, RY-element, MSA-like, and GCN4-motif related to development were present in StATG8 promoters ( Figure 2 and Table 1 ) [ 45 ]. Thus, the diverse StATG8 genes are deeply associated with multiple stress responses and developments.…”
Section: Resultsmentioning
confidence: 99%